Prevalence of enterotoxin a and b genes in Staphylococcus aureus isolated from clinical samples and healthy carriers in Gorgan City, North of Iran - Farideh Kamarehei; Ezzat Allah Ghaemi; Teena Dadgar (Wolters Kluwer Medknow Publications, 2013)
Background: Infections due to Staphylococcus aureus, a nosocomial and community-acquired pathogen, is a major public health problem. Wide range of diseases caused by S. aureus from mild infections of the skin and soft tissue to life threatening diseases which is due to having several virulence factors such as enzymes, toxins and also enterotoxins. Enterotoxin A (SEA) and enterotoxin B (SEB) are superantigens and gasterointestinal toxins causing food poisoning. The sea and seb genes encode SEA and SEB, respectively. The goal of this study was determine the prevalence of sea and seb genes in S. aureus isolated from patients and healthy carriers in Gorgan city, north of Iran. Materials and Methods: 170 isolates of S. aureus (95 from patients and 75 healthy carriers) were collected during 1 year. After identification and purification, DNA extraction was done by phenol - chloroform method. Amplification of sea and seb genes was done by specific primers and polymerase chain reaction method. Results: Among the 170 isolates of S. aureus, 60.6% and 27.1% contained sea and seb genes, respectively. The frequencies of isolates containing sea and seb genes were 58.8% and 61.3%, respectively, in methicillin-resistant Staphylococcus aureus (MRSA) isolates and 23.5% and 28.6%, respectively, in methicillin-sensitive Staphylococcus aureus (MSSA) isolates which were not statistically significant. The frequency of these genes was not related to age, sex and source of isolation in the patients. Conclusion: This study showed that a high proportion of S. aureus isolates carried sea gene, whereas the frequency of seb gene in this region was predictable.